PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANCO NACIONAL COMERCIO TIMOR LESTE (BNCTL) - de Jesus Boavida, Artur Avila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this research to explain the influence of the quality of service for customer satisfaction and loyalty .Of respondents used as many as 120 with the sample collection technique using a purposive the sampling method and criteria for 1 years to customers .Linear regression analysis of data using techniques and was presented with the application of double spss .Test the validity of an instrument of free and variable variable bound having a correlation coefficient with a value above 0.30 positive .The results of konformatori variable quality of services , satisfaction and loyalty of customers have known that all indicators of loading up 0.60 factor          Based on the results of the coefficients determinan 45.48 % capable of being explained this model and the rest 54.51 influenced by other factors .The results of the testing of hypotheses service quality influential significantly to satisfaction .The quality of service influential significantly to customer loyalty and satisfaction influential significantly to customer loyalty .          Based on the discussion of the results of research and the need of advice given to improvements in the dimensions of quality of services especially physical evidence that is the facility as a means to do financial transaction as well as the dimensions of resources in the delivery of tangap clear information to meet the expectations so that customers remain loyal in using the product and is still conducting financial transactions .